The effect of reosorbilact on volumetric and osmoregulatory renal functions in patients with dopamine-dependent compensation for sepsis-induced hypotension - Konovchuk, V. M.; Andrushchak, A. V. (Journal of Education, Health and Sport, 2018)
Objective to study the response of volumetric and osmoregulatory renal functiona to the action of Reosorbilact in dopamine-dependent compensation of sepsis-induced hypotension. Materials and methods. Inclusion criteria - patients with purulent-septic complications in dopamine-dependent compensation (5-10 μg / kg min) according to the initial values: MAP> 70 mmHg, АPs> 95 mmHg, CVP> 4 mmHg, diuresis> 30 ml / h. Control studies - Patients with Systemic Inflammatory Response Syndrome (SIRS) who met the criteria of ICD-10 classification: SIRS, ICD-10: R-65.2. The patients were divided into 4 groups: I gr. and II gr. - control studies (SIRS, n = 25); III gr. and IV gr. - severe sepsis (n = 28). The patients from groups II and IV received an infusion load of Reosorbilact in the amount of 7-8 ml / kg at a rate of 18-20 ml / min. Results. The results of studies on the influence of Reosorbilact on volumetric and osmoregulatory function of the kidneys in patients with severe sepsis in case of dopaminergic hemodynamic compensation (a comparison between groups III and IV) have been presented. The following results were obtained: diuresis, due to a reduction of water reabsorption, increased by 224 ± 58,9% (Δ, P <0,05), sodium clearance by 317 ± 52,5% (Δ, P <0,05), clearance of osmotically active substances - by 240 ± 68,6% (Δ, P <0,05); glomerular filtration rate by 54 ± 11,7% (Δ, P <0,05), the reabsorbed sodium fraction decreased by 1,58 ± 0,29% (Δ, P <0,05), and the reabsorbed fraction of osmotically active substances by 4.2 ± 1.40% (Δ, P <0.05). Conclusions. In dopamine-dependent compensation of sepsis-induced hypotension, there is a decrease in the level of values of glomerular filtration rate (by 41%, P <0.05), sodium clearance (by 17%, P <0.05) and osmotically active substances (by 16% , P <0.05) compared to those in patients with SIRS, which is indicative of the depression of the volumetric and osmoregulatory function. The infusion load with Reosorbilact in patients with compensated sepsis-induced hypotension is realized by increasing the filtration fractions of sodium and osmotically active substances, reducing their reabsorption in the renal tubules, compensatory restoration of volume-dependent reactions characterizing volumetric and osmoregulatory functions of the kidneys.